Issues Of Improving Investment Attractiveness in The Development of The Country’s Economy: Problem and Solution (Eurasian Journal of History, Geography and Economics, 2023)
This article examines the essence of investment attractiveness, the opinions of economists on increasing investment attractiveness in attracting foreign direct investments. Also, the factors influencing the investment attractiveness of our country were analyzed, and internationally recognized indicators assessing the country's business environment and the level of investment risks were discussed. Scientific conclusions and recommendations on increasing investment attractiveness in attracting foreign direct investments have been formulated.